Heated and humidified high flow therapy (HHHFT) in extreme and very preterm neonates with respiratory distress syndrome (RDS): a retrospective cohort from a tertiary care setting in Pakistan - Syed Rehan Ali; Jai K Das; Vikram Kumar Kessani; Fatima Hemani; Iqrar Ali; Sana Memon; Albar Soomro; Rija Zaheer; Khalid N Haque (BMJ Publishing Group, 2024)
Objective To determine the role of heated humidified high flow therapy (HHHFT) as primary respiratory support in spontaneously breathing moderate-late, very and extreme preterm neonates with respiratory distress syndrome (RDS) at a tertiary care hospital from a developing country.Design Retrospective cohort study.Setting Neonatal intensive care unit of Indus Hospital and Health Network, Karachi, Pakistan.Patients All preterm neonates with RDS and who received HHHFT as primary respiratory support were included retrospectively, while neonates with orofacial anomalies, congenital heart and lung diseases other than RDS, abdominal wall defects, encephalopathy, congenital pneumonia and received continuous positive airway pressure or invasive ventilation were excluded.Interventions HHHFT as primary respiratory support for RDS.Main outcome measures Effectiveness, duration, failure rate and complications of HHHFT as a primary respiratory support in moderate-late, very and extremely preterm neonates were evaluated.Results The cohort included 138 neonates during a period of 12 months. The median gestational age was 32 weeks, and the median birth weight was 1607 g. Grade 1-2 RDS was seen in 97%, surfactant instillation was done in 10.8% and HHHFT was provided in all the neonates as primary respiratory support. The total duration of HHHFT support was <1 week in 94% of neonates. Bronchopulmonary dysplasia and pneumothorax until discharge or death were observed in one neonate, haemodynamically significant Patent Ductus Artriosus (HsPDA) in two neonates and intraventricular haemorrhage Grade ≥2 in five neonates, while only one neonate died.Conclusion This study appears to show that HHHFT is a simple, safe, efficient and cheap mode of primary respiratory support that can be given to spontaneously breathing moderate-late, very and extremely preterm neonates with RDS, especially in low- or middle-income countries.